Excitation – emission matrices and synchronous fluorescence spectroscopy for cancer diagnostics in gastrointestinal tract. (June 2016) - Genova, Ts.; Borisova, E.; Penkov, N.; Vladimirov, B.; Zhelyazkova, Al.; Avramov, L.
Abstract: We report the development of an improved fluorescence technique for cancer diagnostics in the gastrointestinal tract. We investigate the fluorescence of ex vivo colorectal (cancerous and healthy) tissue samples using excitation – emission matrix (EEM) and synchronous fluorescence spectroscopy (SFS) steady-state approaches. The obtained results are processed for revealing characteristic fluorescence spectral features with a valuable diagnostic meaning. The main tissue fluorophores, contributing to the observed fluorescence, are tyrosine, tryptophan, NADH, FAD, collagen and elastin. Based on the results of the Mann – Whitney test as useful parameters for differentiation of gastrointestinal cancer from normal mucosa, we suggest using excitation wavelengths in the range for fluorescence spectroscopy and wavelengths intervals of and for SFS.